Changes in the nutritional composition of Thai pangus (Pangasianodon hypophthalamus) pickle during storage at refrigeration temperature: Changes in nutritional composition of fish pickle - Hossain, Md. Ismail; Shikha, Fatema Hoque; Akter, Khaleda (Journal of the Bangladesh Agricultural University, 2018)
There is relation between nutritional composition of fish products and storage conditions. The present study was designed to prepare pickle from dorsal muscle and whole Thai pangus (Pangasianodon hypophthalamus) fish muscle by using different types of food additives and to observe the changes in the nutritional composition, pH and bacterial load of fish pickle during 60 days of storage at refrigeration temperature (5° to 8°C). Mustard oil and soybean oil were used for preparing fish pickle. The quality of fish pickles prepared with either mustard oil or soybean oil, was stable and remained good even after 60 days of storage at refrigeration temperature (5° to 8°C). No bad smell was produced in the pickles. The changes in nutritional composition occurred at this temperature but the rate was slow. Moisture, protein, lipid and pH value decreased as days passed but ash content increased. In case of pickle prepared using soybean oil deterioration rate was higher than the pickle prepared using mustard oil. Bacterial load was higher in soybean oil pickle and also the pickle prepared from whole fish muscle. At this low temperature, bacterial load increased but the rate was slower. Therefore, at refrigeration temperature(5° to 8°C) the pickle remain in acceptable condition quite longer, might be more than 60 days. J. Bangladesh Agril. Univ. 16(3): 553–559, December 2018